The shadow economy, natural resource income, and the effect of economic globalization on carbon emissions: toward a sustainable future - Li, Xueyao; Lau, Wei Theng; Law, Siong Hook; Li, Linwei (John Wiley and Sons, 2025)
The shadow economy, natural resources, and economic globalization are interconnected factors that shape global carbon emissions. Developing effective strategies to mitigate climate change and achieve sustainable development requires understanding the interplay between these factors. This study examines the impact of the shadow economy, natural resource income, and economic globalization on CO2 emissions in APEC countries from 1990 to 2022. The empirical evidence suggests that a 1% increase in the shadow economy leads to a corresponding increase of 0.0861% in CO2 emissions. Economic growth, shadow economy, and economic globalization are positively associated with CO2 emissions in APEC countries. However, electricity supply from renewable sources and income from natural resources are negatively associated with CO2 emissions. Several policy implications need to be considered to address the shadow economy and its potential impact on CO2 emissions in APEC countries. Strengthening the enforcement of environmental laws and regulations is crucial in preventing the shadow economy's negative environmental impact. This includes targeting illegal activities such as logging, poaching, and dumping, which contribute to carbon emissions. Encouraging the transition to clean and sustainable energy sources can help mitigate the shadow economy's contribution to CO2 emissions.